ORGANOLEPTIC QUALITY AND VALUE ADDED OF PULPY RIMAU GERGA LEBONG (Citrus nobilis SP.) ORANGE JUICE WITH EXTRACTION AND DYE ADDITION - Wilda Mikasari; Taufik Hidayat; Lina Ivanti (Jurnal Agroindustri, 2015)
The purpose of this study was to determine the acceptability of society to pulpy RGL  orange juice and value-added products of pulpy RGL orange juice. The research design used was completely randomized design (CRD) factorial with two treatments which were extraction methods (A) and the addition of dyes (B). Results of research showed that orange processing into pulpy RGL orange juice by the addition of dyes and using a press and extractor were not significantly different in organoleptic. Processing pulpy RGL orange juice from 50 kg of raw material could  produce 127 liters juice and can increase the value-added orange RGL 16,300,-/kg with ratio 64 %.